Dr. Andrei-Teodor Pantazi — Deep Plane Facelift — Köln - Pantazi, Andrei-Teodor (DEEPPLANE™, 2026)
Surgeon profile record for Dr. Andrei-Teodor Pantazi, practicing in Köln, Germany. Tracked in the DEEPPLANE™ directory of listed deep plane facelift specialists. Published under CC-BY-4.0.
DPID-003209; accessed 2026-08-14; CC-BY-4.0
Keywords: deep plane facelift; facial plastic surgery; rhytidectomy; SMAS; germany; köln